Fixation of an Anatomically Designed Cementless Stem in Total Hip Arthroplasty - Shigeru Nakamura; Noriyuki Arai; Takateru Kobayashi; Takashi Matsushita (Advances in Orthopedics)
Purpose. The Anatomic Fiber Metal plus stem (Zimmer) is one of the anatomically designed cementless stems to achieve stable fixation by metaphyseal fit. We studied outcomes of cementless total hip arthroplasty using this stem and possible effects of metaphyseal fit on outcomes. Methods. The cementless total hip arthroplasty using this stem was performed for 155 hips. One hundred and thirty-seven hips of 122 patients were followed for 5 to 16 (mean, 9.7) years and entered into the study. The metaphyseal fit was defined as good or poor in an anteroposterior radiograph after surgery. We studied the fixation of the stem and bone reaction on an anteroposterior radiograph at the final followup. Results. Twelve hips had revision, six acetabular components and six acetabular liners. No stem was revised. The biological fixation of the stem was bone ingrown fixation for 136 hips and unstable for one. The metaphyseal fit was good for 83 hips and poor for 54 hips. There were no differences for stem fixation and bone reaction between the two groups. Conclusions. The fixation of the stem was stable at a mean followup of 9.7 years independently from metaphyseal fit.